Acute rheumatic fever and rheumatic heart disease: what's new? - D. Yu. Andriyashkina; N. A. Shostak; A. V. Aksenova; D. V. Abeldyaev (Klinicist)
Rheumatic heart disease (RHD) is a preventable heart disease that remains endemic in developing countries. More than 30 million people in the world suffer from RHD, of which approximately 300,000 die every year, despite the fact that this disease is preventable and treatable. After a period of relative neglect of rheumatic heart diseases due to a decrease in the incidence in developed countries, interest in this problem has increased again over the past decade, due, apparently, to an underestimation of its true prevalence due to the subclinical course of carditis. Research over the past two decades has demonstrated the advantage of diagnosing RHD with echocardiographic screening based on World Heart Federation echocardiographic criteria, which is 10 times greater than the clinical auscultatory picture only and it allowsearly detection of it in patients, while prevention is to be more likely to be effective. Although understanding of the pathogenesis of the disease has advanced in recent years, key issues remain unresolved. Preventing or providing early treatment for streptococcal infections is the most important step in reducing the burden of this disease. The management of women with rheumatic heart disease before, during and after pregnancy remains a serious task requiring the efforts of a multidisciplinary team. In 2015, a civil society movement was launched aimed at raising awareness and supporting countries seeking to solve the RHD problem. In May 2018, the World Health Organization adopted a resolution aimed at intensifying global and national efforts to prevent and combat acute rheumatic fever/RHD. Ultimately, a combination of treatment options, research and advocacy based on existing knowledge and science provides the best opportunity to cope with the burden of rheumatic heart disease. The article summarizes the latest achievements in the science of RHD and presents priorities for current actions and future research.